2013
DOI: 10.1159/000355866
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Nonadherence to Hemodialysis

Abstract: Background: The prevalence of nonadherence to dialysis (NAD) presents a wide variation, depending on the parameters used and demographic regions studied. This study aimed to assess the prevalence and predictors of NAD of patients with chronic kidney disease undergoing hemodialysis (HD). Materials and Methods: This was a cross-sectional study with 255 adult patients receiving HD for >3 months. Skipping a session per month, shortening a session for at least 10 min, phosphorus >7.5 mg/dl, potassium >6.0 mmol/l an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
15
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 24 publications
5
15
2
Order By: Relevance
“…This same association was observed in other studies addressing adherence to different aspects of the treatment (Alkatheri et al, 2014;Dantas et al, 2013;Sgnaolin, Prado & Figueiredo, 2012).…”
Section: Demographic Characteristicssupporting
confidence: 87%
See 1 more Smart Citation
“…This same association was observed in other studies addressing adherence to different aspects of the treatment (Alkatheri et al, 2014;Dantas et al, 2013;Sgnaolin, Prado & Figueiredo, 2012).…”
Section: Demographic Characteristicssupporting
confidence: 87%
“…were higher than those observed in previous studies (Dantas et al, 2013;Ibrahim, Hossam & Belal, 2015).…”
contrasting
confidence: 78%
“…The annual mortality rate in dialysis patients is approximately 21% (77), and the main causes of death are cardiovascular diseases (78,79). Non-adherence to hemodialysis, dietary restrictions and excessive interdialytic fluid weight gain are all risk factors for premature death (80). Refusing treatment or committing suicide is also a reason for premature death in international studies in this population group (78).…”
Section: Mortalitymentioning
confidence: 99%
“…In several other studies conducted on the issue, it was concluded that as age increased so did adherence. [31][32][33] These results can be interpreted as the fact that physical activity decreases in elderly individuals due to physiological processes, and thus they tend to eat and drink less. 34 In conclusion, the participants' adherence to diet and fluid restriction increased in the intervention group after the repetitive and planned training sessions they were given by nurses.…”
Section: Discussionmentioning
confidence: 97%
“…The comparison of the results of the present study in terms of the participants' age demonstrated that nonadherence to diet and fluid restrictions decreased as their age increased. In several other studies conducted on the issue, it was concluded that as age increased so did adherence . These results can be interpreted as the fact that physical activity decreases in elderly individuals due to physiological processes, and thus they tend to eat and drink less…”
Section: Discussionmentioning
confidence: 99%